.5(x+4)=.33(3x-6)

Simple and best practice solution for .5(x+4)=.33(3x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .5(x+4)=.33(3x-6) equation:


.5(x+4)=.33(3x-6)

We simplify the equation to the form, which is simple to understand
.5(x+4)=.33(3x-6)

Reorder the terms in parentheses
+( + 0.5x+2)=.33*(3x-6)

Remove unnecessary parentheses
+ 0.5x+2=+.33+*(+3x-6+)

Reorder the terms in parentheses
+ 0.5x+2=+( + 0.99x-1.98)

Remove unnecessary parentheses
+ 0.5x+2=0.99x-1.98

We move all terms containing x to the left and all other terms to the right.
+ 0.5x-0.99x=-1.98-2

We simplify left and right side of the equation.
-0.49x=-3.98

We divide both sides of the equation by -0.49 to get x.
x=8.12244897959

See similar equations:

| r-6=-6 | | 3x^2-49+200=0 | | 7x-2y+8x+y= | | 4x^4-9x^2+7x+7=0 | | e-10=-3 | | u+6=9 | | 2*3-3+3*4= | | [12-(10-15)]-[6-(7-6)]= | | (p-1)(2p+4)=9 | | 98s^2+648s-5880=0 | | 2s^2+98s-120=0 | | 12d=6+54d | | 98s^2+648s-5881=0 | | 2x+6y=-1 | | x^2+8x+4=9 | | -16n+4=-12n-16 | | y=20+-3x | | 4(7c-1)-2=26c+4 | | 2x^2-9=1 | | 6y-2(y-2)+5= | | 5e+12= | | 4x-4b+x^2b-x^3=0 | | (x+3)=(3x-91) | | (2x+1)=(3x-4) | | ax-bx-a^2+b^2=2a-2b | | ax-bx-a^2+b^2=2ab-2b | | (2x+15)=(6x-57) | | x^7=16870 | | x-2=.5x+5 | | 9y^3-7=y-63y^2 | | .75x-.25x+5=27 | | x-4=25/5 |

Equations solver categories